Аналитическая химия трансплутониевых элементов - Мясоедов Б. Ф. Борис Федорович; Гусева Л. И. Лидия Ивановна; Лебедев И. А. Игорь Александрович; Милюкова М. С. Маргарита Степановна; Чмутова М. К. Марина Константиновна (Аналитическая химия элементов)
На обл. авт. не указаны